2014
DOI: 10.2478/mgr-2014-0008
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Energy Crop Production by Lay People and Farmers Using the Ecosystem Services Approach

Abstract: Perceptions of energy crop production are assessed in this paper. The Görlitz district (Germany) serves as a case study area for this purpose. Semi-structured interviews with farmers and standardized surveys among lay persons were conducted. Many farmers perceive themselves being responsible for providing many ecosystem services. Farmers prefer a regional scale of energy crop cultivation based on conventional crops. Improved legal frameworks and incentives would safeguard equal competition and ecosystem servic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 21 publications
1
4
0
2
Order By: Relevance
“…These results are comparable with other recent studies in Germany [51,71,72]. Other studies indicate a high awareness of these features and the need for their conservation [47,[73][74][75].…”
Section: Importance Of Es For Forest Visitorssupporting
confidence: 83%
See 1 more Smart Citation
“…These results are comparable with other recent studies in Germany [51,71,72]. Other studies indicate a high awareness of these features and the need for their conservation [47,[73][74][75].…”
Section: Importance Of Es For Forest Visitorssupporting
confidence: 83%
“…Also, passers-by were asked to name the importance of several ecosystem services provided by the two forests. The set of selected ecosystem services was similar to that which Lupp et al [51] had selected for agricultural landscapes, however, they had been adapted to forest ecosystems. 102 people completed the questionnaire in this second series.…”
Section: Methodsmentioning
confidence: 90%
“…As Weiland [39], Pöschl et al [40] or Lupp et al [41] point out, responses to climate change warnings can be found in the production of renewable energy by farmers. AD plants fall into the category of facilities for renewable production that should, theoretically, be perceived by the public as less controversial, since they create not only an alternative source of income for farmers (Yiridoe et al [42]) but are also a potential vehicle for rural development (Revelle [43]; Martinat et al [44]; Kostevšek [45]; Warren [46]), by using the waste heat energy released by AD plants for heating local households, farms, etc.…”
Section: Agricultural Ad Plants In Context; Agrarian Change In the Czmentioning
confidence: 99%
“…AD plants fall into the category of facilities for renewable production that should, theoretically, be perceived by the public as less controversial, since they create not only an alternative source of income for farmers (Yiridoe et al [42]) but are also a potential vehicle for rural development (Revelle [43]; Martinat et al [44]; Kostevšek [45]; Warren [46]), by using the waste heat energy released by AD plants for heating local households, farms, etc. Many controversies are linked to the location of such AD plants, however, and to the use of dedicated (food) crops as feedstock for energy production (Lupp et al [41]; Upham [47]; Jørgensen and Andersen [48]). The specifics of the spatial diffusion of AD plants in urban and rural space are commented on in studies by Barnett [49] and Daxiong et al [50], who discuss the crucial role of state support in the initial stages of development in the AD sector.…”
Section: Agricultural Ad Plants In Context; Agrarian Change In the Czmentioning
confidence: 99%
“…Masivní subvenční podpora vlády České republiky pro obnovitelné zdroje, jež byla důsledkem závazku vůči Evropské unii vyrábět do roku 2020 13,5 % elektřiny z obnovitelných zdrojů (Národní akční plán pro rozvoj obnovitelných zdrojů, 2010), způsobila, že více než nástrojem pro omezování dopadů klimatické změny a nástrojem pro podporu lokálního rozvoje se bioplynové stanice staly spíše významným alternativním příjmem farmářů v období, kdy jejich výnosy z tradičních zemědělských aktivit spíše klesají (Doležalová et al 2009, 2014a, 2014b, Konečný 2014, Némethová et al, 2014, Ženka et al 2015. Je proto důležité zkoumat i postoje a názory zemědělců na tuto významnou změnu ve využívání zemědělských pozemků (Lupp et al 2014, Frantál a Prousek 2016), která souvisí s celoevropským příklonem k využívání obnovitelných zdrojů a omezování využívání zdrojů klasických (teoretickou konceptualizaci tohoto problému je možné například nalézt v konceptu energetické transformace -Van der Horst, 2014 nebo Frantál et al 2014).…”
unclassified